Determinants of water conservation practices among opinion leaders: evidence from Kwahu East District, Ghana. Issue 1 (2nd January 2023) - Kwakwa, Paul Adjei; Arku, Frank S.; Nanor, Michael Ayertey
ABSTRACT: This paper assesses the drivers of water conservation practices among opinion leaders in a water-scarce district of Ghana. It was found that the majority of the respondents have a positive attitude towards conservation of water and also felt hurt to see water go to waste. The majority do engage in water conservation practices. Age, environmental concern, income, perceived behaviour control, gender, and emotion were important drivers of water conservation practices. Social norm was found to exert no significant effect on water conservation. Policymakers should involve opinion leaders in the promotion of water conservation behaviour.